APLIKASI MESIN SPINNER UNTUK INDUSTRI KECIL ABON TELUR - Atmika, I.K.A.; Suriadi, I.G.A.K.; Astika, I.M.; Subagia, I.D.A. (Buletin Udayana Mengabdi; Vol 22 No 1 (2023): Buletin Udayana Mengabdi, 2023)
Abon is one of the people's favorite menus made from shredded chicken or beef. This reality has led to the development of many shredded products with various raw materials, such as shredded eel, shredded fish, shredded shrimp, shredded catfish, and even shredded eggs. The model for develo ping shredded eggs from egg raw materials was eyed by a women's business group in Baluk village, Negara sub - district, Jembrana district. The business group in question is the Women Farmers Group (KWT) Pitik Jaya, which began in 2014 by experimenting with their unique product, shredded eggs. The business of making shredded eggs is actually quite prospective because the egg raw materials are produced by the KWT itself. However, this group has problems related to productivity and efficiency, namely in the process of draining shredded oil which is still conventionally done by simply placing shredded coconut on aerated niru. Efforts to overcome the existing problems are carried out by replacing conventional equipment with spinner machines. This machine is multi-functional and is built by a dedicated team so that it can also be used for other product oil extraction. The result of the activity was that the team succeeded in designing and manufacturing a multi-function shredded oil spinner machine with a capacity of 420 eggs per day, so that the use of this machine increased the quality of shredded eggs produced by KWT Pitik Jaya and increased productivity by up to 450%. Keywords: spinner machine, egg shredded, multi function, productivity